(untitled) (Revista LIDER, 2020)
The Autonomous communuty of Andalucía represents 18% of Spain’s population and of its geographical surface (in terms of its physical dimension, it is similar to Portugal). This territory leads the country in organic cattle production, concentrated 62% of the certified animals. Consequent with this, the surface dedicated to feeding meadows, grasses and stubble represents 59% of the area destined to organic production at the national level (MAPA, 2007). With this growth they have had an incidence in the economic compensations that hearders have received in retribution por the possible additional costs derived from the change in production management, specifically with agroenvironmental help, M7, provided within the framework of the (EC) Regulation Nº 1257/1999 on Rural Development (O´Connor, et. al., 2006; Falconer, 2000; Marsden and Banks, 2000; Macfarlane, 1998). These subsidies towards organic ranchers during the period 2001-2006 have had an exponential increase with an annual median rate of 104.6% (CAPA, 2007).